Seh risāla az Thābit b. Qurra : Sāʿathā-yi āftābī, Ḥarakat-i khurshīd u māh, Chahārdah wajhī muḥāṭ dar kurah - Qurra, Thābit b., (Miras Maktoob, ISBN: 9789004365452., 2019)
Thābit b. Qurra (d. 288/901) was a gifted mathematician, scientist and translator of many Greek scientific works, who knew Greek, Syriac and Arabic. He might have spent his entire life in his native Ḥarrān as a money-changer were it not for his chance encounter with Muḥammad b. Mūsā (259/873) of the famous Banū Mūsā brothers, specialists in mathematics and astronomy and among the most important intellectuals of Baghdad at the time. Appreciating his intelligence and his mastery of languages, Muḥammad took Thābit back with him to Baghdad, where he was trained in philosophy, astronomy and mathematics. Thābit then set out on a brilliant career as a translator and author in his own right, writing on all the applied sciences of his time. This facsimile edition of three texts on sundials, solar and lunar motions, and a fourteen-sided solid inside a sphere reproduces the well-known MS Istanbul, Köprülü 948, dated 370/981, copied by Thābit's grandson Ibrāhīm.